Penerapan Manajemen Strategis dalam Meningkatkan Daya Saing UMKM: Studi Kasus Cireng Seuhah Panyileukan - Pina Aulia M; Syahla Mutia Aini; Mila Salbiyah; Asep Saepuloh; Fajar Yunawwirudin; Siti Mardiana (Teewan Journal Solutions, 2025)
This study aims to analyze the implementation of strategic management to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) through a case study of Cireng Seuhah Panyilekann, a local business specializing in traditional Sundanese snack food, cireng (fried tapioca cake). Despite its potential market, this MSME faces challenges related to product quality, distribution, and promotion. This research employs a qualitative approach using a case study method, interviews, and direct observation of the business owners and consumers. The findings reveal that product differentiation strategy, along with a strong focus on quality and innovation in flavor varieties, plays a key role in improving competitiveness. Additionally, effective marketing management through social media and partnerships with distribution agents significantly contribute to market expansion and product visibility. By implementing the right strategies, Cireng Seuhah Panyilekann has successfully improved its position in the local market and strengthened customer loyalty.